Building Trust in Government through Citizen Engagement - Kumagai, Saki; Iorio, Federica (World Bank, Washington, DC, 2020)
This paper explores questions related to trust in government and citizen engagement based on a literature review and consultations with experts and World Bank practitioners. The authors unpack the understanding of what trust is by shedding light on different types of trust and their measurements, explore the relationship between trust and citizen engagement, briefly discuss what governments can do to improve their citizens' trust in institutions, and conclude with areas for further exploration. This paper suggests trust in government and citizen engagement form a mutually reinforcing, interdependent dynamic in policy formation that is affected by common attributes and affect development outcomes and effectiveness. It is one in a series of four notes from the Governance Global Practice on citizen engagement in the areas of fragile, conflict, and violence situations, open government, trust, and emerging technology.